Play Types, Design Principles and Participation in Play: How Is it Possible to Design for Participation in Play? - Jensen, Jens-Ole; Jørgensen, Hanne Hede; Sand, Anne-Lene; Hansen, Janne Hedegaard; Lieberoth, Andreas; Skovbjerg, Helle Marie (EDeR. Educational Design Research, 2023)
Many school-age children have difficulties participating in play and need support to find playmates, take the initiative and structure play. If children do not master these competencies, they risk ending up in a spiral in which they are not given the opportunity to practice playing and develop play competencies. The purpose of the present study is to investigate how design principles in three different play types can be formulated in order to support pedagogues (educators) in developing new play activities with significant potential for participation. In addition, how these design principles cover more general and generic principles are scrutinized. This paper is based on a three-year design-based research study in two Danish schools investigating three play types: creative play, role play and movement play. It also presents four design principles on each play type which were found to support the development of new play activities with inclusive potential. As a theoretical contribution, the design principles of each play type are meta-analysed with the goal of helping pedagogues generate play activities with different participation possibilities. The generic design principles are the essence of play, play practices, play materials and play opportunities for participation.